IMMU-30. UTILIZING A NOVEL MASS CYTOMETRY-BASED IMMUNOMONITORING PLATFORM FOR THE CHARACTERIZATION OF VACCINE-REACTIVE, EPITOPE-SPECIFIC CD8+ T-CELLS IN HLA-A*0201+ PATIENTS WITH K27M+ DIFFUSE MIDLINE GLIOMAS. (11th November 2019) - Taitt, Jared; Watchmaker, Payal; Nejo, Takahide; Almeida, Neil; Okada, Kaori; Shahin, Maryam; Gilbert, Ryan; Mueller, Sabine; Okada, Hideho
Abstract: Diffuse midline glioma (DMG), including diffuse intrinsic pontine glioma (DIPG) constitutes up to 20% of pediatric brain cancer and has a median survival of less than one year. We have identified a novel HLA-A*02:01-restricted neoantigen epitope encompassing the H3.3K27M mutation and implemented a pilot clinical trial through the Pacific Pediatric Neuro-Oncology Consortium (PNOC007). Newly diagnosed DIPG patients who are HLA-A2+ and H3.3K27M+ underwent radiation therapy, and then received the H3.3K27M peptide vaccine and tetanus toxoid (TT) peptide emulsified in Montanide in combination with poly-ICLC every 3 weeks for a total of 24 weeks. Our objective is to characterize vaccine-induced H3.3K27M-specific T-cell subpopulations in peripheral blood mononuclear cells through the evaluation of surface markers correlated with activation, memory, and exhaustion phenotypes utilizing a novel H3.3K27M-specific dextramer-based mass cytometry method. Through this approach, the temporal expansion of vaccine-reactive CD8+ T-cells was observed in all of patients (n = 4) who completed a minimum of 18 weeks on the study. These T-cells were subsequently stratified into discrete clusters on a tSNE plot using canonical CD8+ T-cell markers. Resultant clusters were further classified by their expression profiles, revealing distinct effector memory and exhausted subpopulations. Chronological monitoring of these groups indicates the time course-dependent development and persistence of vaccine-reactive exhausted and effector memory CD8+ T-cells in 75% of patients analyzed. Furthermore, a comparative analysis of myeloid subpopulations revealed an inverse correlation between the expansion of monocytic myeloid-derived suppressor cells (M-MDSCs) and length of enrollment in the trial. Future plans include the analysis of regulatory T-cells (Tregs) and MDSCs of all enrolled patients to solidify the relationship between the length of stay on the study and prevalence of immunosuppressive populations. This methodology offers insight into the progression of vaccine-induced patient immune responses and exhibits promise as a platform that may be extrapolated to other immunotherapies.